1α, 25-Dihydroxyvitamin D3 promotes osteogenesis by promoting Wnt signaling pathway. Issue 174 (November 2017) - Xiong, Yi; Zhang, Yixin; Xin, Na; Yuan, Ying; Zhang, Qin; Gong, Ping; Wu, Yingying
Highlights: 1, 25(OH)2 D3 promotes osteoblasts proliferation and differentiation. 1, 25(OH)2 D3 inhibits FoxO1 through PI3 K/Akt pathway in a time- and dose-dependent manner. 1, 25(OH)2 D3 indirectly promotes the diversion of β-catenin from FoxO1- to Wnt/TCF4-mediated transcription. Abstract: Diabetes mellitus (DM) remarkably affects bone metabolism and causes multiple skeletal disorders, which are associated with the increased oxidative stress that activates Forkhead family of transcription factors (FoxOs). 1α, 25-Dihydroxy vitamin D3 (1, 25(OH)2 D3 ), the hormonally active form of vitamin D, plays a potential role in the prevention of glucose tolerance. However, its mechanism of action in high glucose-induced energy disorders remains unclear. In vitro study shows that 1, 25(OH)2 D3 promotes osteogenesis in high glucose-induced oxidative stress mainly results from increased osteoblasts proliferation and decreased apoptosis. Cells treated with 1, 25(OH)2 D3 exhibit an increased osteogenic differentiation capacity and an elevated level of osteogenic phenotype ( i.e. alkaline phosphatase, collagen 1, osteocalcin, and osteopontin). We also found that the effect of 1, 25(OH)2 D3 on osteogenesis is achieved by FoxO1 inactivation and nuclear exclusion through PI3 K/Akt pathway in a time- and dose-dependent manner. Moreover, the diversion of β-catenin from FoxO1- to Wnt/TCF4-mediated transcription was indirectly promoted by the inactivation of FoxO1. These data together reveals that the activated Wnt/β-catenin signaling is involved in the regulatory action of 1, 25(OH)2 D3 on osteogenesis in oxidative stress. This study also provides a novel understanding of the effect of 1, 25(OH)2 D3 on skeleton in oxidative stress condition.